An Outbreak of Ralstonia pickettii Bloodstream Infection Associated with an Intrinsically Contaminated Normal Saline Solution. (24th January 2017) - Chen, Yin-Yin; Huang, Wan-Tsuei; Chen, Chia-Ping; Sun, Shu-Mei; Kuo, Fu-Mei; Chan, Yu-Jiun; Kuo, Shu-Chen; Wang, Fu-Der
Abstract : OBJECTIVE: Ralstonia pickettii has caused contamination of pharmaceutical solutions in many countries, resulting in healthcare infections or outbreak events. We determined the source of the outbreak of R. pickettii bloodstream infection (BSI). METHODS: This study was conducted in a 3, 000-bed tertiary referral medical center in Taiwan with >8, 500 admissions during May 2015. Patients had been treated in the injection room or chemotherapy room at outpatient departments, emergency department, or hospital wards. All patients who were culture positive for R. pickettii from May 3 to June 11, 2015, were eligible for the study. The aim of the survey was to conduct clinical epidemiological and microbiological investigations to identify possible sources of infection. RESULTS: We collected 57 R. pickettii –positive specimens from 30 case patients. We performed 24 blood cultures; 14 of these revealed >2 specimens and 6 used fluid withdrawn from Port-a-Cath implantable venous access devices. All patients received an injection of 20 mL 0.9% normal saline via catheter flushing. In addition, 2 unopened ampules of normal saline solution (20 mL) were confirmed positive for R. pickettii . The Taiwan Centers for Disease Control and Prevention performed sampling and testing of the same manufactured batch and identified the same strain of R. pickettii . Pulsed-field gel electrophoresis tests revealed that all clinical isolates had similarity of >90%, validating the outbreak of the same clone of R. pickettii . CONCLUSIONS: R. pickettii can grow in saline solutions and cause bloodstream infections. Hospital monitoring mechanisms are extremely important measures in identifying and ending such outbreaks. Infect Control Hosp Epidemiol 2017;38:444–448